Strategi Pembelajaran Komunikatif Metode Think Talk Write dengan Media Gambar dalam Meningkatkan Keterampilan Menulis Karangan - Sholihah, Lailatus; Kamto, Kamto (Sekolah Tinggi Agama Islam Pati, 2023)
Think Talk Write learning model is one type of communicative learning model that is built through the process of thinking, speaking, and writing. This research uses picture media to help students in writing the content of the essay. The purpose of this study was to determine the existence of a communicative learning strategy using the Think Talk Write method with image media in improving the essay writing skills of grade III students at MI Hidayatul Islam Gembong. This type of research is field research with a qualitative approach. with a qualitative approach. This research was conducted in Mi in May-June 2022. Data collection methods used were observation, interviews and documentation from the principal, third grade teacher, and data collection methods used observation, interviews and documentation from the principal, grade III teachers, grade III students and the waka of curriculum of MI Hidayatul Islam Gembong. After the data is collected, it is done by data that supports the formulated research objectives. The data analysis technique used from Miles a Huberman is a technique of finding and compiling data obtained systematically through the process of summarising data, presenting data, and drawing conclusions so that it can be easily understood and can be informed to others. The results of the study prove that the communicative learning strategy of the Think Talk Write method with picture media in improving the skills of writing skills of grade III students at MI Hidayatul Islam Gembong are as follows: First, implementing a Learning Strategy here the teacher is required to be able to use a good learning strategy because the strategy is able to provide convenience for educators to students. Therefore, teachers are required to have a learning strategy before learning takes place; second, the importance of learning media, the existence of learning media is able to help educators in learning to convey a material to be given so that children can be very easy and understand when given learning media; third, the importance of essay writing skills, the importance of essay writing skills is able to make students like to write essays. the importance of essay writing skills is able to make students like to write more because the purpose of this study is for children to prefer writing. of this study so that children prefer to write and can write well and in accordance with the applicable spelling because in accordance with the applicable spelling, therefore more emphasis is placed on essay writing skills. writing skills.